A retrospective analysis of the growth of non generisized proton pump inhibtors after the launch of generic molecules in the same therapeutic class - Mangalmurti, Ajit Madhav (My University, 2009)
Abstract Background The South African Healthcare landscape has changed dramatically over the last two years with the implementation of mandatory substitution, single exit pricing and prescribed minimum benefits. The private market for medicines is becoming more competitive and commoditized. Between July 2004 and June 2005 there were 119 generic registrations at the Medicines Control Council. In the US and Canada research has been conducted on the change in prescribing behaviour induced through incentive based formularies and the impact of generic medicines on healthcare costs. This research protocol aims to build on this body of knowledge by analysing sales trends within a therapeutic class after the launch of a generic molecule in the same class. This research investigates how the introduction of generics may impact the growth of the innovator molecules and subsequent generics. The therapeutic class Acid Pump Inhibitors has been selected. Method Unit sales of Proton Pump Inhibitors are drawn monthly from sales in the total private market. They are then grouped by molecule and comparisons are drawn between the originator and it’s generic to determine association. This is also done at the aggregate level where the originators form one group and generics the second group. Each aggregate group’s average growth in the therapeutic class is then calculated to determine the aggregate group’s evolution index. Data Analysis Data is analysed through descriptive and interpretative statistics. The descriptive statistics establish a relationship between generisized molecules and the non generisized molecules. A t-test for two independent means is used to test the hypothesis that the non generisized molecules in the therapeutic class have a significant higher growth. Conclusion The results demonstrate that the number of units sold of the generisized molecules increase as they become more affordable, however contrary to intuition the number of iv units sold of the non generisized molecules also increase. The research shows that there is a statistically significant greater growth, albeit on a smaller base, of the non generisized molecules over generisized molecules.
Keywords: generic molecules; therapeutic equivalency; non-generisized proton pump inhibitors